Regeneration of Tree Legume - Albizia procera (Roxb.) Benth. Through Tissue Culture - Ahlawat, S. P. (Indian Forester, 1997)
Plantlets were produced in-vitro from hypocotyl and nodal bud explants of tree legume -Albizia procera. Initially explants were reared for 8 weeks on MS + 0.1-2.0 mg/l either of IAA, IBA, NAA, 2,4-D,BAP KN and in combination of BAP and NAA/IBA. Multiple shoots differentiated directly on the explant and from callus of explant. A combination of MS + 1.0 BAP + 0.5 mg/l NAA gave best differentiation and proliferation of shoots. This combination enhanced shoot proliferation rate 13- 16 fold in 180 days upon serial transfer of cultures. Nodal segments yielded more shoots than hypocotyl explant. Rooting was achieved in Â½ MS + IBA 1.5 mg/l + 1.0% activated charcoal. The plantlets acclimatized stepwise and successfully transferred to soil.